Esquizofrenia e toxoplasmose: aspectos clínicos, cognição e funcionalidade - Leandro Saldanha Nunes (2018)
Introduction: The association between Schizophrenia and Toxoplasmosis has received great prominence in recent decades. Epidemiological studies point to a greater seroprevalence of Toxoplasmosis in the population with schizophrenia and an increased risk of developing the mental disorder in those individuals infected acutely and chronically by the infectious agent Toxoplasma gondii. Several harmful mechanisms have been proposed, however, more evidence is needed to determine the infection as a marker of clinical, cognitive and functional severity in Schizophrenia. Objective: The aim of this study is to analize the comparison between the group of pacientes with Schizophrenia and Toxoplasmosis vs. pacientes with Schizophrenia and without Toxoplasmosis, in regarless to the clinical profile, cognitive and functional performance. Method: Cross-sectional study, with convenience sample, n = 54 subjects with schizophrenia, stratified into two groups, IgG positive (n = 26) and IgG negative (n = 28) for T. gondii. Clinical severity parameters for schizophrenia were evaluated, among them, number of hospitalizations, attempts at self-extermination, antipsychotic dose, use of clozapine and symptomatology, the latter analyzed by PANSS (Positive and Negative Symptoms Scale in Schizophrenia). The cognitive domains evaluated were verbal episodic memory, executive functions and attention. For that, the RAVLT tests (Rey's Auditory-Verbal Learning Test), 5-points, Verbal Fluency and Semantics and Stroop were applied. For the evaluation of the functionality, the FAST (Functional Assessment Short Test) scale was applied. For all tests, the significance level of 95% (α = 0.05) was adopted. Results: There were no significant differences between the groups when compared to the severity of the positive and negative symptoms of Schizophrenia, markers of clinical severity, neurocognitive tests and functional performance. Conclusion: the results showed that the chronic infection with Toxoplasmosis was not related to clinical severity as well as to the worse cognitive and functional performance in patients with Schizophrenia. Further studies and amplified samples are needed.